2001
DOI: 10.1002/ijpg.240
|View full text |Cite
|
Sign up to set email alerts
|

Towards a (re)theorisation of the historical geography of nationalism in diasporas: the Irish diaspora as an exemplar

Abstract: The strength of diasporic nationalism is characterised by an uneven historical geography, with different diasporic communities functioning as`hotbeds' of nationalism at different times. Mapping and explaining these historical geographies is of importance if the cultural and political experiences of diasporic existence are to be understood. It is towards a critical interrogation of the conceptual tools available to accomplish this task that this paper is dedicated. Based upon a reading of social scienti®c liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The geography of fluid social relations in the global city might provide a context for 'making oneself' through acts of self-identification alongside others who share similar social positions, but in places where social relations remain dominantly structured in other ways, it is impossible simply to imagine 'belonging' to particular groups, especially where those groups believe that they have previously engaged in geographical projects associated with 'making history'. In this sense social theorists, and particularly those engaged in pursuing post-modern ideas of identification, need to consider more seriously the importance of geography in shaping social relations over time (Boyle 2001;Massey 1999). The situatedness of everyday life through which groups express their identities implies that there are also external boundaries on the possible identities to which groups may aspire.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The geography of fluid social relations in the global city might provide a context for 'making oneself' through acts of self-identification alongside others who share similar social positions, but in places where social relations remain dominantly structured in other ways, it is impossible simply to imagine 'belonging' to particular groups, especially where those groups believe that they have previously engaged in geographical projects associated with 'making history'. In this sense social theorists, and particularly those engaged in pursuing post-modern ideas of identification, need to consider more seriously the importance of geography in shaping social relations over time (Boyle 2001;Massey 1999). The situatedness of everyday life through which groups express their identities implies that there are also external boundaries on the possible identities to which groups may aspire.…”
Section: Discussionmentioning
confidence: 98%
“…A final twist which we wish to introduce to this study of English migrants in Scotland relates to the literatures on diasporic identities and identification (Boyle 2001(Boyle , 2002Brah 1996;Clifford 1994;Maffesoli 1996;Mitchell 1997;Walter 2001). Although the term 'diaspora' is used dominantly in relation to forced migration (e.g.…”
Section: The Service Class Identity and Nationalismmentioning
confidence: 99%
“…Both Newman and O'Tuathail demonstrated that the geographical imagination of a nation-state results from a contest between various geographical imaginations (Newman 2000;O'Tuathail 2004). Boyle also revealed that the specificity of diasporas, notably the Irish one, needs to be studied much more critically than has been done (Boyle 2001). The case of the Irish diaspora provides an undisputable example of how emigrants do maintain a strong attachment to a highly territorialized conception of the nation as the island (Lyons 2006), thus directly questioning the assumption of the de-reterritorialising impact of diasporas both on national cultures and national political agendas.…”
Section: Some Implications Of Insisting Upon the Importance Of Reterrmentioning
confidence: 93%
“…Two of the papers in that special issue explored the potential of the concepts of diaspora (Boyle, 2001) and transnationalism (Bailey, 2001) to provide bridges between population geography and new human geographies. Boyle (2001: 431) focused on diasporic nationalism and proposed 'fresh ways in which the historical geography of diasporic nationalism might be approached'.…”
Section: Introductionmentioning
confidence: 99%